1993
DOI: 10.1042/bj2960827
|View full text |Cite
|
Sign up to set email alerts
|

Calponin phosphorylation in vitro and in intact muscle

Abstract: Calponin, a thin-filament-associated protein implicated in the regulation of smooth-muscle contraction, is phosphorylated in vitro by protein kinase C and Ca2+/calmodulin-dependent protein kinase II [Winder and Walsh (1990) J. Biol. Chem. 265, 10148-10155] and dephosphorylated by a type 2A protein phosphatase [Winder, Pato and Walsh (1992) Biochem. J. 286, 197-203]. Unphosphorylated calponin binds to actin and inhibits the actin-activated myosin MgATPase; these properties are lost on phosphorylation. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 48 publications
3
61
0
Order By: Relevance
“…The signal for the postulated agonist-induced decrease in actin affinity is still unknown, but the CaP redistribution has been shown to be dependent on protein kinase C (PKC) activity (Parker et al 1994), suggesting a phosphorylation event. CaP can be phosphorylated by PKC in vitro (Winder et al 1993). Also, several groups have reported that CaP can be phosphorylated in vivo (Winder et al 1993;Mino, Yuasa, Naka & Tanaka, 1995;Pohl et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The signal for the postulated agonist-induced decrease in actin affinity is still unknown, but the CaP redistribution has been shown to be dependent on protein kinase C (PKC) activity (Parker et al 1994), suggesting a phosphorylation event. CaP can be phosphorylated by PKC in vitro (Winder et al 1993). Also, several groups have reported that CaP can be phosphorylated in vivo (Winder et al 1993;Mino, Yuasa, Naka & Tanaka, 1995;Pohl et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Also, several groups have reported that CaP can be phosphorylated in vivo (Winder et al 1993;Mino, Yuasa, Naka & Tanaka, 1995;Pohl et al 1997). Winder et al (1993) also showed that upon phosphorylation in vitro, CaP's binding affinity to actin is diminished significantly. Phosphorylation may trigger a loss of CaP binding affinity to actin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calponin is a 34-kDa smooth muscle protein that binds actin (3), myosin (12), Ca 2ϩ -binding proteins (13,14), and tropomyosin (15). In vitro calponin inhibits the actomyosin ATPase activity upon binding to actin, and this inhibition is reversed by its phosphorylation (16) or by its interaction with Ca 2ϩ -binding proteins such as calmodulin or caltropin (13,14). Consequently, it has been suggested that calponin may have a role in controlling smooth muscle contraction.…”
mentioning
confidence: 99%
“…Therefore it has been proposed that additional regulatory mechanisms may exist at the level of the thin filament [18][19][20], and calponin may play a role in this signal transduction pathway. For example, calponin inhibits the actin-activated Mg-ATPase activity of phosphorylated smooth muscle myosin, and this inhibition is regulated by phosphorylation-dephosphorylation of calponin [5,6,[21][22][23]. In itro motility assays demonstrated that calponin inhibits the relative movement of actin and myosin filaments [24,25].…”
Section: Introductionmentioning
confidence: 99%